Delivery of Aerosolized Liposomal Amikacin as a Novel Approach for the Treatment of Nontuberculous Mycobacteria in an Experimental Model of Pulmonary Infection - Rose, Sasha J.; Neville, Mary E.; Gupta, Renu; Bermudez, Luiz E. (PLOS ONE, 2014)
Pulmonary infections caused by nontuberculous mycobacteria (NTM) are an increasing problem in individuals with chronic lung conditions and current therapies are lacking. We investigated the activity of liposomal amikacin for inhalation (LAI) against NTM in vitro as well as in a murine model of respiratory infection. Macrophage monolayers were infected with three strains of Mycobacterium avium, two strains of Mycobacterium abscessus, and exposed to LAI or free amikacin for 4 days before enumerating bacterial survival. Respiratory infection was established in mice by intranasal inoculation with M. avium and allowing three weeks for the infection to progress. Three different regimens of inhaled LAI were compared to inhaled saline and parenterally administered free amikacin over a 28 day period. Bacteria recovered from the mice were analyzed for acquired resistance to amikacin. In vitro, liposomal amikacin for inhalation was more effective than free amikacin in eliminating both intracellular M. avium and M. abscessus. In vivo, inhaled LAI demonstrated similar effectiveness to a ∼25% higher total dose of parenterally administered amikacin at reducing M. avium in the lungs when compared to inhaled saline. Additionally, there was no acquired resistance to amikacin observed after the treatment regimen. The data suggest that LAI has the potential to be an effective therapy against NTM respiratory infections in humans.